Editing and the Institutionalization of Cinema, 1913-1917 - Shaw, Nick; Keil, Charlie (Cinémas)

(untitled) (Cinémas, 2018)
How was editing imagined during the transitional period, as cinema became an institution? How closely did the trade press’s representation of editing, as a formal system subject to change, align with trends apparent on the screen? Did commentators of the day register editing’s changing functions? To what degree can we detect an “editing consciousness” within the trade press, and how did it operate in the crucial years of 1913-17? To better answer these questions, this essay looks at the terminology that writers employed when writing about editing during these years, the advisories that they issued, and the factors that may have influenced their conceptions of editing. These observations will help us define with more precision how the industry reconciled itself to editing’s ascendancy and reaffirm the uneven contours of the process of institutionalization.